Effects of four diets on the metabolism of megalopa metamorphosis of the mud crab, Scylla paramamosain - Keyi Ma; Zhiqiang Liu; Guangde Qiao; Lingbo Ma; Fengying Zhang; Ming Zhao; Chunyan Ma; Wei Wang (Frontiers in Marine Science, 2023)
Dietary intake is an essential source of energy and nutrients, and plays an irreplaceable role in the breeding of S. paramamosain seedlings. In this study, live Artemia nauplii (LA), compound feeds (CF), frozen copepods (FC) and frozen adult Artemia (FA) were utilized as feed during the megalopa stage. To determine the impact that diet has on the metabolism of crablets that underwent metamorphosis from the megalopa stage, analyses of both metabolomics and fatty acid content were conducted. In the LC-MS-based metabolomics analysis, a total of 104, 205 and 83 significantly different metabolites (SDMs) were identified after being fed with FC, FA, and CF, respectively, as compared to the LA group. Furthermore, significant differences in KEGG compounds among the three comparisons exhibited similarity and were mainly associated with categories such as “Lipids”, “Hormones and transmitters”, and “Peptides”. The fatty acid content analysis indicated that the ΣMUFA was significantly higher in the LA and CF groups compared to the other two groups. In contrast, the highest level of ΣPUFA was found in the LA group. In addition, the CF group showed significantly higher expression levels of the fatty acid synthesis genes, FAS and ACC . Conversely, the expression level of the fatty acid decomposition-related gene CPT1 was the highest in the LA group. In comparison with the FA group, the expression level of FABP3 was significantly decreased in the LA and CF groups. In summary, there were significant differences observed in the metabolic profiles of crablets that metamorphosed from the megalopa under different diets. Our experimental results suggested that LA is more advantageous in the cultivation of the S. paramamosain megalopa compared to the other three diets. While it remains a diet that cannot be entirely substituted at present, LA has the potential to improve the culture performance of the S. paramamosain megalopa. The current study could provide valuable data into the development of artificial diets necessary for the future of the mud crab seedling breeding industry.